A Matter of Fidelity: Self‐Sorting Behavior of Di‐Gold Metallotweezers. Issue 35 (22nd May 2019) - Ibáñez, Susana; Peris, Eduardo
Abstract: Cation‐induced high selective self‐sorting is observed for reactions involving a series of di‐gold metallotweezers. The variation of the nature of the arms of the tweezers (benzo‐imidazolylidene or pyrene‐imidazolylidene), or the rigid bis‐alkynyl linker (anthracenyl‐bis‐alkynyl or xanthenyl‐bis‐alkynyl), induces different type of self‐sorting events upon addition of a metal cation (Cu +, Tl +, or Ag + ). Combining two tweezers with the same arms and different linkers produces narcissistic self‐sorting. The combination of tweezers with the same linker and different ligands at the arms produces social self‐sorting. Abstract : Sort yourself out : Highly selective metallophilic‐directed narcissistic and social self‐sorting is observed in a series of di‐gold metallotweezers.